Visão baseada em recursos no setor público: uma análise dos desempenhos, recursos e capacidades de duas zonas eleitorais do tre-rn - Andrade, Thiago Capistrano (2019)
Since the redemocratization of the country, the Electoral Justice has obtained, in addition to a normative and administrative evolution, a significant technological advance, especially through the use of the electronic ballot box, which made the counting of votes faster. Inserted in the management model of Public Administration, it has exercised strategic management seeking, above all, efficiency, effectiveness and effectiveness of its results. One of the theoretical strands that permeate strategic management research is that of Resource Based Vision (VBR). It is a theoretical perspective originating from the private sector, which is concerned with the organization's resources and capabilities as a means of achieving competitive advantage, and which gained repercussion after the creation of the VRIO organizational analysis model. Thus, considering that the holding of elections is one of the purposes of the Electoral Justice and that the counting of votes is an important activity of the election work, this research aimed to analyze what are the main resources and strategic capacities in the activity of closing and totaling. of the results of the voting that make the most efficient the performance of two TRE-RN Electoral Zones. Therefore, using the VRIO model, an analysis of the resources and capacities of two TRE-RN Electoral Zones was performed, relating them to their performances in past elections and comparing them with each other, in order to identify which ones are differentials. for efficiency of your work. The applied method has a qualitative approach, with exploratory / descriptive objective, carried out ex post facto, from a single case study, in two TRE-RN Electoral Zones. As a result, the tasks performed by the Zones, their objectives and performance in elections were described, followed by the identification of resources and strategic capabilities, which were submitted to the VRIO analysis. From this analysis, the importance of resources and capabilities and how they contribute to the end-of-day voting activity was described. In all, five sources of competitive parity, two sources of temporary competitive advantage and six sources of sustainable competitive advantage were identified, thus showing their competitive implications and how they impact the efficiency of the studied zones. This research has yielded results that can contribute to the management of Electoral Justice, with a methodology that can be replicated in other TRE-RN activities and sectors. This is the suggestion for further research